A Risk Situation Threatening Public Law: Example of Fanaticism in Turkey - Çankaya, Ibrahim; Bek, Hafiz (Jurnal Cita Hukum, 2026)
This study was conducted to examine the views of football fans regarding fanaticism, which poses a risk to public law. Data were collected from responses to the Football Fanaticism Scale. The working group consisted of Uşakspor football team fans in the Turkish Football 2nd League. Among the supporters of the team, 1568 people were interviewed on a voluntary basis. It was evaluated as a scale of 1530, which was answered completely. It has been determined that the fans have a high level of team belonging and a low level of violent tendencies. The violent tendency and team belonging of woman fans are higher than many fans. The propensity to violence among the fans in the 18-24 age group is higher than the violence tendency among the fans over the age of 30. The tendency for violence among self-employed fans is higher than among public servants and retired fans. Only literate fans have a higher tendency to violence than university graduates. The violent tendency and team belonging of the fans who are interested in sports are higher than the fans who are not interested in sports. The violent tendency of the fans who never go to the team's matches is higher than the violent tendency of the fans who constantly go to the team's matches. The violent tendencies of fans who watch the matches of the team on television are higher than the fans who do not watch the matches on the television. There was a positive relationship between the tendency to violence and belonging to the team.